Toxic Effects of Purified Microcystins from Soil Blue-Green Alga Oscillatoria pseudogeminata on Tomato Plant Lycopersicon esculentum - Al-Sultan et al. (مجلة بغداد للعلوم)
The current study included the isolation, purification and cultivation of blue-green alga Oscillatoria pseudogeminata G.Schmidle from soil using the BG-11liquid culture medium for 60 days of cultivation. The growth constant (k) and generation time (G) were measured which (K=0.144) and (G=2.09 days).